Copy number variation analysis and methylome profiling of a GNAQ-mutant primary meningeal melanocytic tumor and its liver metastasis - Küsters-Vandevelde, Heidi; Kölsche, Christian; Deimling, Andreas von (Experimental and molecular pathology, 2017)
Primary meningeal melanocytic tumors have genetic similarities with uveal melanomas, including GNAQ or GNA11 mutations. While BAP1 mutations and loss of chromosome 3 have adverse prognostic meaning in uveal melanoma, genetic alterations associated with metastasis have not been investigated in primary meningeal melanocytic tumors. We describe a 43-year-old female with a GNAQ-mutated, BAP1-wt melanocytic tumor originating in the parietal brain region and liver metastases 4years after initial diagnosis. After repeated surgery and chemotherapy she was treated with the immunomodulatory agent ipilimumab. Tissue from the primary and recurrent intracranial tumor (histologically originally diagnosed as intermediate-grade melanocytoma resp. melanoma) and from the liver metastasis was investigated for genome-wide copy number variations and DNA methylation profile. Complete loss of 10p and 19p, partial loss of 16p and a small deletion on 10q were only present in the liver metastasis and not in the intracranial tumors. The DNA methylation profiles of the intracranial tumors and the liver metastasis resembled those of meningeal melanocytomas. In conclusion, in this report we show that a distant metastasis of a meningeal melanocytic tumor has a similar methylation profile as the primary tumor and suggest that particular copy number variations may be associated with metastatic behavior.
Available online 11 December 2016
Gesehen am 31.10.2018